A Comparative Histochemical Study of Mucous Cells in Odontogenic Cysts. (29th October 2013) - Carim, Ridwaana; Mahomed, Farzana
Abstract : The diagnosis of a glandular odontogenic cyst (GOC) on an incisional biopsy continues to remain a diagnostic challenge for the histopathologist. A marker for distinguishing GOC from odontogenic cysts with mucous metaplasia is thus needed in routine pathology practice. This study aimed to determine the histochemical composition of the mucous cells in the GOC and to compare the findings with the mucous cells in odontogenic cysts that show overlapping histomorphological features with the GOC. GOCs (n = 10 ), dentigerous cysts (DCs) (n = 9 ), and radicular cysts (RCs) (n = 8 ) with mucous metaplasia were stained using the combined alcian blue(pH 2.5)-PAS histochemical technique. The cysts were evaluated for the frequencies of acidic- (type I), neutral- (type II) and mixed- (acidic and neutral (type III)) mucin containing cells. Significant differences were found between the levels of type I, type II, and type III mucous cells within the 3 cyst types, GOC (P = 0.006 ), DC (P = 0.0004 ), and RC (P = 0.0017 ), which all showed a predominance of type III mucous cells. There were, however, no significant differences for each mucous cell type between the 3 cyst types. GOC thus appears to share the same histochemical mucin phenotype with the mucous cells in DC and RC.